Palliative Care Services for Patients with Noncancer Diseases in Outpatient Clinics Across Canada: A National Survey Study - Asia Estis-Deaton; Daphna Grossman; Tania Johannsen; Kathleen Milne; Leah Salvage; Michael Bonares (Journal of Palliative Medicine, 2026)
Background: The palliative care needs of patients with noncancer diseases are increasingly recognized, yet the prevalence, models, and delivery of outpatient specialist palliative care for these populations remain understudied. Objective: To describe outpatient palliative care clinics for noncancer diseases across Canada, including clinic prevalence and models of care. Methods: Cross-sectional survey study of practicing Canadian palliative care physicians recruited nationally. Quantitative data were analyzed descriptively, and qualitative data were analyzed using thematic analysis. Results: Eighty-eight physicians responded (response rate = 13.2%). Fifty-six physicians from seven provinces completed the survey, representing 49 noncancer palliative care clinics. Most clinics (71%) were disease-agnostic or focused on neurological or transplant populations. Majority were stand-alone clinics (55.5%, 95% confidence interval [CI] = 37%–72%), with the remainder embedded in disease-specific clinics (37%, 95% CI = 28%–63%). Joint specialist-palliative visits were uncommon (32%; 95% CI = 18%–51%). Few initial visits were virtual (2%; interquartile range [IQR] = 0%–5% for telephone and 0%–6% for video), and rural patients constituted a minority of caseloads (median = 20%; IQR = 10%–50%). Referral criteria varied, with some incorporating prognosis and functional scores. Barriers included logistical constraints, staffing, and variable disease specialists and institutional supports. Communication and collaboration were identified as key strategies to overcome barriers. Conclusions: While outpatient palliative care clinics for noncancer diseases in Canada appear to be growing, survey respondents identified ongoing challenges including variable referral practices, limited resources, and gaps in rural access. These preliminary findings should be interpreted with caution given the response rate and missing data. Nevertheless, they underscore the need to address barriers to equitable and timely palliative care access in these populations.